2020
DOI: 10.1093/eurpub/ckaa166.205
|View full text |Cite
|
Sign up to set email alerts
|

Parents' knowledge about complementary feeding: an integrative review

Abstract: Currently, authorities and specialists in child development and public health have been concerned with the growth and nutritional status of children, especially due to the uncontrollable increase in overweight / obesity that has occurred in recent years. Obesity causes organic-functional complications, such as chronic-degenerative diseases (diabetes, high blood pressure, coronary heart disease), and psychosocial complications, such as withdrawal from social relationships, shame, exclusion and disturbances in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Ignorance of the rules of child nutrition and macroand microelement intake results in errors during meal preparation [23,29]. The authors of research from 2010 observed that the average total energy intake in children aged 1-3 years old was 1217.5 kcal (SD = 331.8), which was 122% of the recommended daily requirement [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ignorance of the rules of child nutrition and macroand microelement intake results in errors during meal preparation [23,29]. The authors of research from 2010 observed that the average total energy intake in children aged 1-3 years old was 1217.5 kcal (SD = 331.8), which was 122% of the recommended daily requirement [24].…”
Section: Discussionmentioning
confidence: 99%
“…A mother's diet during pregnancy and the child's nutrition up to the age of three have the most significant impact on the child's health [4]. According to research, even though parents' knowledge of children's nutrition is growing, parents still make many mistakes in feeding their children [23].…”
Section: Introductionmentioning
confidence: 99%
“…A recent integrative review showed that European parents' knowledge about child feeding, particularly complementary feeding (e.g., when to first start the introduction of solid foods), is far from optimal ( 19 ). In contrast, an online quantitative survey conducted in the UK evaluated parents' understanding of feeding guidelines, reporting high knowledge of the recommendations ( 20 ).…”
Section: Introductionmentioning
confidence: 99%